Association between smoking status and handgrip strength in Korean male adults: based on Korea National Health and Nutrition Examination Survey 2016–2019 - Cho, Eunbyul; Soh, Hi Sun; Lee, Jae-Ryun; Yun, Jieun; Bae, Woo Kyung; Lee, Hyejin (Frontiers in Medicine, 2023)
Abstract Background: Smoking is a well-known risk factor of frailty. Handgrip strength (HGS) is highly representative of muscular strength and is used in the diagnosis of frailty; however, the relationship between smoking and HGS is not clear. We evaluated the relationship between smoking status and HGS. Objectives: This study aimed to evaluate the association between HGS and smoking status. Methods: We enrolled adult males between the ages of 19 and 80 years who participated in the Korea National Health and Nutrition Examination Survey VII–VIII. A chi-square test and ANOVA were performed to compare the mean handgrip strength (mean HGS) between non-smokers, ex-smokers, and current smokers. Logistic regression analysis was performed to determine the association between the smoking status and mean HGS, and additional analyses were performed by dividing subgroups by age. Results: A total of 7,649 participants were analyzed. When the mean HGS and mean dominant HGS were compared according to smoking status, HGS was higher in the right hand (p-value = 0.03) and left hand (p-value < 0.001) in the order of current smokers, ex-smokers, and non-smokers. Comparing HGS of stronger hands, the mean HGS ex-smokers [aOR, (95% confidence interval): 0.61(0.46–0.82)] and current smokers: 0.55(0.38–0.78) was higher than that of non-smokers. When subgroup analysis was performed according to age, current smokers aged > 60 years had a higher grip strength than non-smokers. Conclusions: Current smokers had a stronger mean HGS than that of ex-smokers and non-smokers. Current smokers older than 60 years appeared to have a stronger mean HGS than ex-smokers and non-smokers of the same age group.